2014
DOI: 10.1007/s10551-014-2513-0
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility in China: A Corporate Governance Approach

Abstract: This study examines the effects of corporate governance mechanisms on CSR performance in an emerging economy, China. Because of the need of gaining legitimacy in the new institutional context, Chinese firms have to adopt global CSR practices in order to remain competitive. Using the corporate governance framework, this study examines how board composition, ownership, and TMT composition influence corporate social performance. The propositions are tested using data gathered from 471 firms in China. By and large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
319
4
19

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(424 citation statements)
references
References 80 publications
(124 reference statements)
18
319
4
19
Order By: Relevance
“…e percentage of companies from Asia Paci c is impacted by the predominance of Chinese and Japanese companies. e Chinese companies use CSP due to the need to gain legitimacy and remain competitive in the global market (Lau, Lu & Liang, 2016;Wang, Tong, Takeuchi & George, 2016). In addition to these factors, China is one of the countries with the most D-CSP regulations .…”
Section: Methodsmentioning
confidence: 99%
“…e percentage of companies from Asia Paci c is impacted by the predominance of Chinese and Japanese companies. e Chinese companies use CSP due to the need to gain legitimacy and remain competitive in the global market (Lau, Lu & Liang, 2016;Wang, Tong, Takeuchi & George, 2016). In addition to these factors, China is one of the countries with the most D-CSP regulations .…”
Section: Methodsmentioning
confidence: 99%
“…Dam and Scholtens (2013) [54] found that more concentrated ownership goes hand in hand with poorer CSR policies because shareholders may feel that they provide public goods at a higher price. Although the findings of Lau et al (2015) [53] indicated that CSR is positively influenced by ownership concentration in Brazil, most scholars have concluded that there is a negative relationship between concentrated ownership and social responsibility. Cormier et al (2009) [54] argued that firms with concentrated ownership are not as responsive as others to public questioning because controlling shareholders would not like to share information with others.…”
Section: Hypothesis 4 (H4)mentioning
confidence: 99%
“…However, a firm with high ownership concentration will exhibit reduced diversity and CSR [53]. Dam and Scholtens (2013) [54] found that more concentrated ownership goes hand in hand with poorer CSR policies because shareholders may feel that they provide public goods at a higher price.…”
Section: Hypothesis 4 (H4)mentioning
confidence: 99%
“…awareness of the quality and content of listed firms' overall social reporting activities (Marquis and Qian, 2014;Hung et al, 2015;Lau et al, 2016;and Luo et al, 2016).…”
mentioning
confidence: 99%